Briquette Shape Roles in Carbothermal Reduction Process of Limonitic Laterite Nickel - Abdul, Fakhreza; Ridarto, Afif Maulana Yusuf; Setiyorini, Yuli; Setyowati, Vuri Ayu; Pintowantoro, Sungging (International Journal of Integrated Engineering, 2024)
Carbothermic reduction of laterite nickel ore is currently the focus of many researchers. This process uses a relatively lower temperature of operation than the smelting. Therefore, the carbothermal reduction process has a relatively lower primary energy demand and CO2 gas emissions. This research examines the appropriate briquette form to achieve the optimum concentration, recovery of nickel, and selectivity factors of nickel, as well as analyzes the compounds/phases formed. The briquette in this study was formed into three different geometries, i.e., the pillow, spherical, and cylindrical forms. First, this research was carried out by mixing the prepared materials and forming them into selected briquette forms. Second, the formed briquettes were put into a crucible. Third, the coal-limestone bed mixture was used to cover the briquettes. Then, the carbothermic reduction process was started by heating to 700 oC for 2 hours and continued to 1400 oC for 6 hours. Finally, the magnetic separation process was performed to separate the reduced briquettes. As a result, the pillow-shaped briquette obtained better results at 6.74% Ni, with a nickel recovery of 96.20% and a selectivity factor value of 10.39. The compounds formed after carbothermic reduction process products include FeNi, Fe3Si, and SiO2. In a spherical-shaped briquette, Fe3O4 and Mg2SiO4 were found in the reduced product, indicating impurities in the reduced briquettes.